Energy Efficient Multi-Sink Hybrid Data gathering Framework for Smart Agriculture Monitoring System in Wireless Sensor Network - Biswal, Sanjay Kumar; Sahoo, Sampa; Mohanty, Prabhudutta (Journal of Neonatal Surgery, 2025)
Wireless Sensor Network (WSN) is a key emerging technology helps in providing efficient and reliable solutions for modernizing agricultural farming with minimal Human involvement. This approach has become more defined and evidence-based data gathering approach in refining throughput by elevating usage of resource. The proposed approach presents a Multi-Sink Hybrid Data-gathering WSN-based framework for the smart agriculture Monitoring system with minimal energy consumption. At first, anptimized node deployment strategy is used to divide the sensing field into logical cells. Each cell has a leader node designed for sensing and communication activity. The primary objective of the projected approach is to reduce traffic overhead while monitoring sensing entities like temperature, soil moisture, and humidity of the soil for irrigation thereby minimizing energy conservation of the sensor network. Over the years small sensor nodes have been designed to monitor environmental conditions to reduce energy consumption. The adoption of new clustering technology & optimization of routing protocols led to an increase in the battery lifetime in WSN. The proposed framework adopts a load balancing scheme, the Silent and Zero Start (SZS) approach exploits redundant data communication to increase energy conservation. We also adopted a modified acknowledgment scheme that helps to achieve reliability during communication. The performance analysis of the proposed framework shows a better result than some existing smart agriculture monitoring systems